Pakistan : What's the Best Way to Invest in Private School? - World Bank (World Bank, Washington, DC, 2019)
Private schools that cater to low-income students are popular with parents seeking alternatives to government schools. But these private schools, which are often owned by local entrepreneurs, may lack the resources and incentives to expand enrollment or improve quality. They generally operate in markets where access to credit is limited and where there aren't loan products tailored to their needs. This means that any improvements have to be financed through school fees or their own funds. When donors and investors step in to provide support to private schools, they tend to focus on larger operators with a chain of schools, which typically implies selective funding to a limited number of schools rather than broad support to the schooling market. Is this the best way to support private schools that cater to poor families? Could supporting the entire market, rather than select schools—or chains—lead to more competitive pressure to invest in quality improvements that promote students’ learning? And is a market for loans for private schools sustainable?